Control of Vessel Space Order on Import through Forwarder at PT. Sejahtera Transindo Lestari - Phamendyta Aldaning Azaria; Riska Aulia Umry (Budapest International Research and Critics University, 2022)
The purpose of the research is to find out control of vessel space order on import through forwarder at PT. Sejahtera Transindo Lestari. This type of research is descriptive research. This study aims to provide an overview or explanation regarding the control of ship space reservations on imports through forwarders at PT. Sejahtera Transindo Lestari. The focus of this research is a comprehensive description of the condition of the shipping industry. Sources of data from this study using primary data and secondary data. The results of the study indicate that there are several factors that influence the control of ship space reservations on imports through forwarders at PT. Sejahtera Transindo Lestari, namely ocean freight renewal, contract rate and spot rate pricing, container port growth, as well as port congestion and ship delays.